Archival Management at the University of Lampung - Shandi Patria Airlangga; Teguh Faisal; Meidiana Ciptasari Ratna Nugraha (Universitas Lampung, 2018)
Humans as creatures who have limited memories need archives to restore the memories systematically. Archiving has been known since the writing method developed and peoples make records of their archives. Nowadays the archive is valued as a guideline for institutions to make decision. Universities, as the education institutions in carrying out its functions, universities produce archives that comply with the Law No. 43 of 2009 on Archives as the basis for managing archives in universities. The University of Lampung and ANRI have agreed on MoU to work together in applying and disseminating the importance of filing on November 21, 2014. The Rector of University of Lampung Decree No. 4 of 2016 was established on April 20, 2016 regarding the Archive Retention Schedule (JRA), in addition to fulfilling the mandate contained. In Article 48 of Act Number 43 of 2009 concerning the obligation for state universities to have a JRA in archival management, it is also useful as a guide for archival management officials and employees in carrying out their duties. Innovation from ANRI also continued to be socialized to the University of Lampung in realizing efficient archive management. Keywords: Archival, Management, MoU, University of Lampung, ANRI.